Pattern of Bacterial Infection in Orthopedic Department at Tertiary Care Hospital - Sajid Akhtar, Muzammil Ahmad Shah, Dilawar Khan, Muhammad Shabir, Ahmad Karim., Waleed Anwar Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To identify prevalence of different type of bacteria among patient of different diseases in orthopedic department. Methodology: It was cross-sectional study done in Department of Orthopedics, Saidu Group of Teaching Hospital Swat from 1st February 2022 to 31st January 2023. A total of 209 patients, both male and female with age between 10 years to 70 were included. The specimens including pus and/or fluids were collected from the effected site by orthopedic consultants for culture and sensitivity. Results: Bacteria were isolated from 198(94.70%) samples while 11(5.30%) samples showed no growth of any bacteria. Among them staphylococcus aureus was isolated from 117 samples making 55.98% of total samples, pseudomonas aeruginosa was isolated from 44 samples making 21.03% of total samples, Escherichia coli was isolated from 32 samples making 15.31% of total samples. Three species of Citrobacter (1.43%) and two species of Enterobacter spp. (0.95%) were also isolated from the samples. Sixty seven samples were taken from post-operative site, 44 samples from abscess, 39 samples from osteomyelitis, 38 samples from Septic arthritis and 21 from diabetic Foot. Pseudomonas aeruginosa (49.27%) was most prevalent in postoperative infections, Staphylococcus aureus (94.87%) in osteomyelitis, Pseudomonas aeruginosa (52.38%) in diabetic foot, Staphylococcus aureus (68.18%) in soft tissue abscess also in Septic Arthritis (86.84%). Practical Implication: The pattern of microbial infection varies in post-operative infections, septic arthritis, osteomyelitis, diabetic foot ulcer and abscess. Conclusion: Bacterial infections in musculoskeletal system are common and on time identification with use of specific antibiotics may help in early recovery and abutting complications. Keywords: Prevalence, Orthopedics, Post-operative site, Abscess, Osteomyelitis, Septic arthritis, Diabetic foot